2004
DOI: 10.1002/lt.20154
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin-G subclass antidonor reactivity in transplant recipients

Abstract: Outcomes may differ after kidney transplantation compared to combined liver-kidney transplantation. In animal models, distinct patterns of antidonor immunoglobulin (Ig) G subclasses are associated with either rejection or transplant tolerance. Flow cytometry has increased the sensitivity of antidonor immunoglobulin detection. We compared antidonor IgG subclass responses in kidney transplant recipients to those in recipients of liver or multiorgan grafts. In this study of 19 organ (kidney, liver, pancreas) tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…12,[22][23][24][25][26][27][28] The initial appearance of strong complementfixing IgG1 and IgG3 antibodies may expand to weak or noncomplement-binding IgG2 and IgG4 antibodies; therefore, various profiles of IgG subclasses are seen in transplant recipients. 29 Previous studies have failed to firmly identify a predictive subclass pattern due to the heterogeneous IgG subclass response and to several technical [30][31][32] and methodological limitations, mainly related to the small number of recipients included 26,33,34 or the lack of precise clinical and histologic phenotyping of the ABMR injury. 23,24 The integration of different properties of circulating anti-HLA DSA, including HLA class specificity, strength, complementbinding capacity and IgG subclasses, allowed us to identify three distinct clinical and histologic patterns of antibody-mediated injury, as recognized by the latest Banff classification: aABMR, sABMR, and ABMR-free.…”
Section: Discussionmentioning
confidence: 99%
“…12,[22][23][24][25][26][27][28] The initial appearance of strong complementfixing IgG1 and IgG3 antibodies may expand to weak or noncomplement-binding IgG2 and IgG4 antibodies; therefore, various profiles of IgG subclasses are seen in transplant recipients. 29 Previous studies have failed to firmly identify a predictive subclass pattern due to the heterogeneous IgG subclass response and to several technical [30][31][32] and methodological limitations, mainly related to the small number of recipients included 26,33,34 or the lack of precise clinical and histologic phenotyping of the ABMR injury. 23,24 The integration of different properties of circulating anti-HLA DSA, including HLA class specificity, strength, complementbinding capacity and IgG subclasses, allowed us to identify three distinct clinical and histologic patterns of antibody-mediated injury, as recognized by the latest Banff classification: aABMR, sABMR, and ABMR-free.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, complement-fixing HLA class II antibodies did not affect graft survival, even though they were associated with C4d deposition. Anti-donor antibodies of the strong complementfixing subclass IgG3 were present in three patients with acute rejection but not in stable patients, whereas the latter had a significant rise only in the non-complement-fixing IgG4 subclass (58). In mice, non-complement-fixing IgG alloantibodies are associated with graft acceptance but can also activate endothelial cells to produce chemokines and promote rejection (56).…”
Section: Antibody and Complement Effects On Endotheliummentioning
confidence: 99%
“…Complement fixation is strongly associated with the ability of antibody to mediate AHR in animal models (56) and in humans (57,58). Recipients with anti-donor HLA class I antibodies that fix C4d to FlowPRA beads had inferior graft survival compared with those that did not, the latter having a similar outcome to patients with no anti-donor antibody (57).…”
Section: Antibody and Complement Effects On Endotheliummentioning
confidence: 99%
“…Several studies have attempted to characterize the repertoire of DSA immunoglobulin subclasses in transplant recipients and correlate them with allograft outcomes. Their results have suggested that IgG3 DSA are a driver of acute AMR [103, 104], while IgG4 correlates more closely with subclinical AMR [105] and chronic rejection [106, 107]. Moreover, different terminal moieties in the Fc glycan of IgG have been demonstrated to change the inflammatory nature of antibodies.…”
Section: Mechanisms Of Antibody Mediated Graft Injurymentioning
confidence: 99%